Cooperating over losses and competing over gains: A social dilemma experiment - Alessandro Ispano; Peter Schwardmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Evidence from studies in international relations, the politics of reform, collective action and price competition suggests that economic agents in social dilemma situations cooperate more to avoid losses than in the pursuit of gains. To test whether the prospect of losses can induce cooperation, we let experimental subjects play the travelers dilemma in the gain and loss domain. Subjects cooperate substantially more over losses. Furthermore, our results suggest that this treatment effect is best explained by reference-dependent risk preferences and reference-dependent strategic sophistication. We discuss the implications of our results and relate our findings to other experimental games played in the loss domain.
Keywords: C90; D01; D03; D81; 330; travelers dilemma; loss domain; diminishing sensitivity; strategic sophistication